2016
DOI: 10.1016/j.jallcom.2016.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Structural, dielectric and magnetic properties of Ba3SrLn2Fe2Nb8O30 (Ln = La, Nd, Sm) filled tungsten bronze ceramics

Abstract: Structural, dielectric and magnetic properties have been investigated for Ba 3 SrLn 2 Fe 2 Nb 8 O 30 (Ln=La, Nd, Sm) ceramics. The single phase tetragonal filled tungsten bronze structure in space group P4/mbm is obtained for Ba 3 SrLa 2 Fe 2 Nb 8 O 30 , while such tungsten bronze major phase is determined together with minor amount of secondary phases in Ba 3 SrNd 2 Fe 2 Nb 8 O 30 and Ba 3 SrSm 2 Fe 2 Nb 8 O 30. The saturated magnetic hysteresis loops with enhanced M r are obtained in the present ceramics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…synthesized Ba6CoNb9O30 ceramics to indicate nature of the relaxor ferroelectric, a wide dielectric peak and frequency dispersion. The maximum dielectric constant value of Ba6CoNb9O30 ceramics is about 100 higher than the Ba3SrLn2Fe2Nb8O30 ceramics as previously reported [8,11]. Guo et.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…synthesized Ba6CoNb9O30 ceramics to indicate nature of the relaxor ferroelectric, a wide dielectric peak and frequency dispersion. The maximum dielectric constant value of Ba6CoNb9O30 ceramics is about 100 higher than the Ba3SrLn2Fe2Nb8O30 ceramics as previously reported [8,11]. Guo et.…”
Section: Introductionsupporting
confidence: 67%
“…When ionic radius decreases, permittivity maximum temperature (Tmax) increases. This is because of the occupancy of different valence and ionic radii in the same position, resulting in the Fe/Nb dipole deviating from the center, and the long-range order at low temperature is disrupted by the distribution field, thus facilitating the formation of relaxor ferroelectrics [8][9][10]. In this article, we also investigated the influence of A site substitution, but we used Co to dope B site.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric crystals with tetragonal tungsten bronze structure (TTB) are important ferroelectric materials. Their interesting dielectric and ferroelectric properties have attracted extensive research activities studying on their structural and physical properties due to the compositional flexibility [1,2]. The TTB structure consists of a complex array of distorted BO6 octahedron sharing corners in such a way, that three different types of interstices (pentagonal A2, square A1, and trigonal C sites)…”
Section: Introductionmentioning
confidence: 99%
“…Ganguly et al [8] have been reported the structural, dielectric and electrical studies of Ba 5 SmTi 3 Nb 7 O 30 ferroelectric ceramics. Wang Chen et al [9] …”
Section: Introductionmentioning
confidence: 99%